Experimental evaluation of certain herbs against chlorpyrifos-induced oxidative stress and toxicity in poultry - Bharathi, P; Reddy, A Gopala; Kalakumar, B; Madhuri, D (The Indian Journal of Animal Sciences, 2011)
Male broiler chicks (1 225), day-old, were randomly divided into 15 groups consisting of 15 chicks in each group. Group 1 was maintained as basal diet control and group 2 on chlorpyrifos (CPS) @ 100 ppm in feed throughout 6 weeks as iron toxic control without any treatment. Groups 3 to 15 were maintained on CPS @ 100 ppm in feed for the 4 weeks (28 days) of study and thereafter, administered with different herbs and their combinations for remaining 2 weeks. The blood samples were drawn from wing vein on day 28 and day 42 from the birds in each group for the assay of erythrocytic superoxide dismutase (SOD) and catalase. Sera samples were separated from the blood for the estimation of alanine transaminase (ALT) and serum creatinine. The birds were sacrificed at the end of 6th week and tissues were collected for the assay of GSH and TBARS in liver and brain homogenates. The activity of SOD, catalase and ALT, and the concentration of TBARS and serum creatinine were increased significantly, while the concentration of total proteins and tissue GSH decreased significantly in all the groups as compared to basal diet control and the values showed significant improvement in groups 3–15 that were treated during the last 2 weeks. It is concluded that chlorpyrifos induces toxicity by generating reactive oxygen species and antioxidant herbs are useful in treating the chlorpyrifosinduced toxicity.